Multivalent Display of SARS-CoV-2 Spike (RBD Domain) of COVID-19 to Nanomaterial, Protein Ferritin Nanocages - Umesh Kalathiya (Biomolecules, 2021)
SARS-CoV-2, or COVID-19, has a devastating effect on our society, both in terms of quality of life and death rates; hence, there is an urgent need for developing safe and effective therapeutics against SARS-CoV-2. The most promising strategy to fight against this deadly virus is to develop an effective vaccine. Internalization of SARS-CoV-2 into the human host cell mainly occurs through the binding of the coronavirus spike protein (a trimeric surface glycoprotein) to the human angiotensin-converting enzyme 2 (ACE2) receptor. The spike-ACE2 protein–protein interaction is mediated through the receptor-binding domain (RBD) of the spike protein. Mutations in the spike RBD can significantly alter interactions with the ACE2 host receptor. Due to its important role in virus transmission, the spike RBD is considered to be one of the key molecular targets for vaccine development. In this study, a spike RBD-based subunit vaccine was designed by utilizing a ferritin protein nanocage as a scaffold. Several fusion protein constructs were designed in silico by connecting the spike RBD via a synthetic linker (different sizes) to different ferritin subunits (H-ferritin and L-ferritin). The stability and the dynamics of the engineered nanocage constructs were tested by extensive molecular dynamics simulation (MDS). Based on our MDS analysis, a five amino acid-based short linker (S-Linker) was the most effective for displaying the spike RBD over the surface of ferritin. The behavior of the spike RBD binding regions from the designed chimeric nanocages with the ACE2 receptor was highlighted. These data propose an effective multivalent synthetic nanocage, which might form the basis for new vaccine therapeutics designed against viruses such as SARS-CoV-2.